2009
DOI: 10.1108/17439130910987558
|View full text |Cite
|
Sign up to set email alerts
|

The relationship among board of director characteristics, corporate social performance and corporate financial performance

Abstract: Purpose -The purpose of this paper is to investigate the link between qualitative measures of a firm's Board of Directors and its corporate social performance (CSP). Design/methodology/approach -CSP is a function of qualitative measures of a firm's Board of Directors, as well as firm risk and financial performance. A longitudinal sample of 104 Canadian firms is used. Findings -Board independence is positively related to social performance but shareholder orientation is not. In addition, a positive relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 57 publications
(132 reference statements)
4
70
0
3
Order By: Relevance
“…Similarly, Dunn and Sainty [74] studied a sample of 104 Canadian firms and concluded that companies with more independent boards generally obtain higher levels of CSP. In the same vein, Jo and Harjoto [59] studied a sample of nearly 15,000 U.S. firms, and found a positive connection between the independence of the board and CSP.…”
Section: Linking Board Independence and Corporate Social Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Dunn and Sainty [74] studied a sample of 104 Canadian firms and concluded that companies with more independent boards generally obtain higher levels of CSP. In the same vein, Jo and Harjoto [59] studied a sample of nearly 15,000 U.S. firms, and found a positive connection between the independence of the board and CSP.…”
Section: Linking Board Independence and Corporate Social Performancementioning
confidence: 99%
“…On the one hand, the independence of a firm's board has been defined as the extent to which the board of directors operates independently from executive directors [182] and it has been usually measured as the percentage of board members who are non-executive directors, outside directors and independent directors [49,50,67,183]. On the other hand, Dunn and Sainty [74] state that "the essence of CSP is the recognition or awareness that there are multiple stakeholders against which a business has responsibility towards in the longer term". This definition involves broadening the focus on financial targets and including social and environmental targets, producing a need to measure and assess economic, social and environmental performance.…”
mentioning
confidence: 99%
“…In a one-tier board system, boards of directors are the highest governing body that sets company's policies and makes important strategic decisions. The board represents shareholders and other stakeholders to monitor and influence decisions and policies made by top management which have to be in line with shareholders' expectations (Dunn and Sainty, 2009 independent non-executive directors [4] and executive directors. This is to ensure the establishment of an effective board in the company.…”
mentioning
confidence: 99%
“…As independent directors are less dependent on CEO's goodwill and image than executive directors, they can closely monitor and control management's activities (Jizi et al 2013). In relation with the resource dependence theory, shareholder's interest and corporate image can be best ensured by the independent board (Dunn &Sainty, 2009;Webb, 2004). This study also assumes that higher number of independent directors in the board is expected to yield better CSR disclosures.…”
Section: Board Independencementioning
confidence: 98%
“…Though there are substantial number of literatures on board attributes and CSR (Graaf & Herkstroter, 2007;Dunn & Sainty, 2009;Rao & Tilt, 2015;Ayuso et al, 2007 andMalik, 2015), no empirical study is found on Bangladeshi banking sector investigating the relationship between various diversified board composition factors and extent of CSR reporting.…”
Section: Literature Reviewmentioning
confidence: 99%